Peranan Agama dalam Restorasi Peradaban Umat Islam Menurut Muhammad Fethullah Gulen - Usman Syihab (Universitas Darussalam Gontor, 2014)
This article examines Muhammad Fethullah Gulen’s thought on the roles of religion in reconstruction of a civilization. The article analyzes the problem anatomy of the Ummah, concepts of civilization, relationship between identity and civilization, religion and its roles in formation of civilization identity, the “essential” conditions for Muslim’s renaissance, and the role of Islamic scholars in the renaissance process. The article reveals Gulen’s idea, that the Muslim’ crises is internal in nature, and not because of others, it is a “liability to be colonize” attitude. Religion has a vital role in construction of a civilization identity. A religion can be pillar of a civilization is a religion that has lofty goals, able to apply moral values, upgrade spiritual quality, and fulfill human’s soul needs. According to Gulen, every civilization has its links with the past and its cultural haritage, and that any attempt to reconstruct a future civilization has to consider its own cultural roots. Thus, a civilization is neither a life adopted from colonials nor values that has been deprived from its own noble values. The article, using philosophical, historical and sociological approaches, tries to analyze the “essential” conditions that able to restore Islamic civilization and spawn Muslim’s renaissance, mainly; a) moral-spiritual, b) knowledge, c) aesthetic, and d) love. The article also explains critically the roles and missions of ulamâ in making “resurrection from the grave”, renaissance and total reform of the ummah.